The role of trust in shaping successor commitment in family businesses - Teddy Saputra; Burhan Bungin; Thomas S Kaihatu (Journal of Innovation in Business and Economics, 2025)
This study investigates the relationship between trust and commitment between predecessor and successor generations in family businesses. Using a survey of 203 successors, the research examines how different dimensions of trust—affect-based, cognition-based, and interpersonal—shape successor commitment. The findings reveal that only affect-based trust significantly influences all forms of successor commitment, including affective, normative, calculative, and imperative commitment. In contrast, cognition-based trust and interpersonal trust do not exhibit a significant impact. These results suggest that emotional validation and recognition from the predecessor generation play a critical role in fostering successor commitment. Managing intergenerational trust—particularly affect-based trust—effectively can enhance successor engagement and support the long-term continuity of family businesses.